Development and Effectiveness of MilleaLab-Based Virtual Reality Learning Media Integrated with Deep Learning in Biology Class - Mukhoyyaroh, Qiswatun; Firman Wilantika, Cancan; Khofifah, Siti; Muntasar Hakim, Kaka (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2025)
Biology materials related to bioprocesses are inherently abstract and often difficult for students to comprehend because the learning media traditionally rely on textbooks and 2D images, which fail to describe the ongoing bioprocesses in sufficient detail. Therefore, additional teaching aids are required. Furthermore, learning should not only emphasize cognitive aspects but also address affective and psychomotor domains. The purpose of this study was to evaluate the feasibility and effectiveness of VR-based learning media, developed using the MilleaLab platform, on the circulatory system to support deep learning among high school students. The research employed R&D approach using the ADDIE model. The sample consisted of 11th-grade students from MA Darul Falah Rangkasbitung. The research instruments included a preliminary study interview guide, product trial observation sheets, feasibility questionnaires for material, language, and media experts, feasibility questionnaires for small-group, large-group, and real-world testing, as well as user response questionnaires. The results showed that the average product feasibility score was 91%, categorized as highly feasible. The effectiveness test of the VR learning media yielded a score of 0.89, also categorized as high. Student responses to the learning media reached 94%, categorized as highly feasible, while teacher responses were 95%, likewise categorized as highly feasible.